PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR ADVERTISING PRINTING MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herman Syaputra; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is for test about working capital effect for profitability in advertising printing media listed at Indonesia stock exchange. So working capital that indicated with cash turn over, receivable turn over and inventory turn over, and profitability that indicated with return on investment (ROI). Data used at this research was secunder data. Population of this research was advertising printing media sector what listed at Indonesian stock exchange. And sampling method used for this research is purposive sampling to take some data on 5 companies for 5 years to get 25 financial report. This research need classical assumption test include normality test, multikolonierity test, heterokedastisity test and auto correlation test. To analyzed this data need multiple linier regression analyzed, t test,f test and determination coefisien test. To analyzed this data need software program SPSS 16. The result of this research show that capital working variabels that indicated with cash turn over for partial test (t test) have no significant effect with return on investment (ROI) meanwhile inventory turn over have no significant effect with return on investment (ROI). And simultaneous result (f test) show that all independent variabels have positif effect to return on investment (ROI). Adjusted R square value about 0,626 and result show 62,6% ROI can explain independent of capital working that indicated cash turn over, receivable turn over and inventory turn over. And 37,4% as other variabels. Key Word : capital working, cash turn over, receivable turn over, inventory turn over, profitability (ROI)